Artemis Fowl : the eternity code - Colfer, Eoin. (New York : Hyperion Books For Children, 2003)
Artemis Fowl creates an extraordinarily powerful computer with stolen fairy technology, but his business deal hopes go sour when a Chicago businessman steals his invention and mortally wounds Artemis's loyal bodyguard.
"Miramax books."
Pub Weekly
7.1
5-8
Keywords: Fairies -- Fiction; Magic -- Fiction; Fathers and sons -- Fiction; Science fiction; England -- Fiction; Fantasy; Fairies -- Fiction; Magic -- Fiction; Father-son relationship -- Fiction; England -- Fiction; Fantasy fiction